First record of Xyleborus bispinatus (Coleoptera: Curculionidae, Scolytinae) and evidence of stable populations in the Iberian Peninsula - Gallego, Diego; Sora, Nicolò Di; Molina, Noelia; Gonzalez-Rosa, Eudaldo; Mas, Hugo; Knížek, Miloš (Zootaxa, 2022)
We present the first record of the tropical ambrosia beetle Xyleborus bispinatus in the Iberian Peninsula, collected in traps located in Murcia, Alicante and Valencia provinces (Spain). Insects have been captured in baited traps of long-time trapping networks (ESFP, MUFFET, RAT and SAMFIX) installed in Eastern Spain. Several individuals (410) of X. bispinatus have been collected in seven locations, first in 2009 in Murcia Region, and from 2018 to 2021 in Valencia Region. No attacks by X. bispinatus have been detected on plants thus far, and therefore the host plant in Spain remains unknown. Stable X. bispinatus populations have been detected in a wide area of central Valencian province. We may consider this as an alarming scenario that should be kept under surveillance by maintaining the current trapping network and intensifying the search for the host plants.